Răspuns :
[tex] \frac{5}{2x - 1} = \\ \frac{5}{2 \times 3 - 1} = \frac{5}{5} = 1 \\ \frac{5}{2 \times 1 - 1} = 5[/tex]
[tex] \frac{5}{2x - 1} \: nr. \: intreg \: = > 2x - 1 \: \epsilon \: D_{5}[/tex]
[tex]D_{5} = \begin{Bmatrix}
\pm1, \pm5
\end{Bmatrix}[/tex]
[tex]2x - 1 = - 1 [/tex]
[tex]2x = - 1 + 1[/tex]
[tex]2x = 0[/tex]
[tex]x = \frac{0}{2} [/tex]
[tex]x = 0[/tex]
[tex]2x - 1 = 1[/tex]
[tex]2x = 1 + 1[/tex]
[tex]2x = 2[/tex]
[tex]x = \frac{2}{2} [/tex]
[tex]x = 1[/tex]
[tex]2x - 1 = - 5[/tex]
[tex]2x = - 5 + 1[/tex]
[tex]2x = - 4[/tex]
[tex]x = - \frac{4}{2} [/tex]
[tex]x = - 2[/tex]
[tex]2x - 1 = 5[/tex]
[tex]2x = 5 + 1[/tex]
[tex]2x = 6[/tex]
[tex]x = \frac{6}{2} [/tex]
[tex]x = 3[/tex]
[tex] = > x \: \epsilon \: \begin{Bmatrix}
- 2 ,0,1,3
\end{Bmatrix}[/tex]
[tex]pt.\:x=-2=>\frac{5}{2\times{(-2)}-1}=\frac{5}{-4-1}=\frac{5}{-5}=-1\:\epsilon\:Z[/tex]
[tex]pt.\:x=0=>\frac{5}{2\times0-1}=\frac{5}{0-1}=\frac{5}{-1}=-5\:\epsilon\:Z[/tex]
[tex]pt.\:x=1=>\frac{5}{2\times1-1}=>\frac{5}{2-1}=\frac{5}{1}=5\:\epsilon\:Z[/tex]
[tex]pt.\:x=3=>\frac{5}{2\times3-1}=\frac{5}{6-1}=\frac{5}{5}=1\:\epsilon\:Z[/tex]
[tex]D_{5} = \begin{Bmatrix}
\pm1, \pm5
\end{Bmatrix}[/tex]
[tex]2x - 1 = - 1 [/tex]
[tex]2x = - 1 + 1[/tex]
[tex]2x = 0[/tex]
[tex]x = \frac{0}{2} [/tex]
[tex]x = 0[/tex]
[tex]2x - 1 = 1[/tex]
[tex]2x = 1 + 1[/tex]
[tex]2x = 2[/tex]
[tex]x = \frac{2}{2} [/tex]
[tex]x = 1[/tex]
[tex]2x - 1 = - 5[/tex]
[tex]2x = - 5 + 1[/tex]
[tex]2x = - 4[/tex]
[tex]x = - \frac{4}{2} [/tex]
[tex]x = - 2[/tex]
[tex]2x - 1 = 5[/tex]
[tex]2x = 5 + 1[/tex]
[tex]2x = 6[/tex]
[tex]x = \frac{6}{2} [/tex]
[tex]x = 3[/tex]
[tex] = > x \: \epsilon \: \begin{Bmatrix}
- 2 ,0,1,3
\end{Bmatrix}[/tex]
[tex]pt.\:x=-2=>\frac{5}{2\times{(-2)}-1}=\frac{5}{-4-1}=\frac{5}{-5}=-1\:\epsilon\:Z[/tex]
[tex]pt.\:x=0=>\frac{5}{2\times0-1}=\frac{5}{0-1}=\frac{5}{-1}=-5\:\epsilon\:Z[/tex]
[tex]pt.\:x=1=>\frac{5}{2\times1-1}=>\frac{5}{2-1}=\frac{5}{1}=5\:\epsilon\:Z[/tex]
[tex]pt.\:x=3=>\frac{5}{2\times3-1}=\frac{5}{6-1}=\frac{5}{5}=1\:\epsilon\:Z[/tex]